(3JPcQI GHf eJhjg aj CMcGe GdLhGgQ hGdCYQGas - (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj,J (B468 (3g` s
(3ChdgG (B:s
(3gPg JPcQI JTJed Ydi HjGf CMcGe GdeYdheGJ hChGUagG hJLeY Edi GdGjLGR ai Gdbhd EYde Gf GdeYdheGJ GLeY dGJNQL Yf bSeg JJQOO Hjf Gdfai hGdGKHGJ s
(3BNQgG (B:s
(3jfJgi HCMcGe GdHcG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG Jedc HGSe eMeO Hf YHO Gddg bGSe Hf CMeO GdhUGdi GdbGSeis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs